Downlink performance of DS CDMA system for LEO satellite communication links - Umrani Abdul Waheed (2008)
Demand for mobile and personal communications is growing at a rapid pace, both in terms of the number of potential users and new high-speed services. Meeting this demand is challenging since wireless communications are subject to major constraints such as: a complex fading channel, a scarce usable radio spectrum.